Are Canadian orthopaedic surgeons and American orthopaedic surgeons on par? A Canadian practice survey of orthopaedic traumatologists. Issue 2 (3rd June 2023) - Doxey, Stephen; Only, Arthur J.; Milshteyn, Michael; Cunningham, Brian P.; Cannada, Lisa K.
Abstract: Objectives: The purpose of this study was to obtain information on Canadian orthopaedic trauma surgeon practices and salary demographics. It was hypothesized that most of the practicing surgeons recognize specific practice aspects (compensation, call schedule, operating room availability, and provided support staff) as key factors in employment opportunity evaluation. Design: Cross-sectional survey study. Setting: Orthopaedic Trauma Association (OTA) practice surveys. Participants: All active Canadian members of the OTA were eligible to participate. Main Outcome Measurement: A 50-question survey was sent through email to OTA members assessing physician, practice, and compensation metrics of Canadian orthopaedic traumatologists. Results: Fifty-two of 113 Canadian OTA members participated giving a response rate of 46%. All surgeons worked in an academic practice, either for a university (83%) or community hospital (17%). Only 2% of surgeons have changed jobs in the last 5 years, and over 73% of surgeons maintain the same place of employment during their careers. Most had an available dedicated orthopaedic trauma operating room (73%). The majority indicated having residents (71%) and fellows (63%) as support staff. Many reported completing 300–500 cases per year (42%), which decreased during COVID-19 for 50% of surgeons. The most common reported compensation was between 400, 000 and 600, 000 US dollars (25%) with many working 4–6 call shifts a month (48%) and 51–70 hours a week (48%). Conclusion: This study demonstrated the varying practice and physician economic variables currently in Canada. The identification and continued surveillance of these employment variables will allow for transparency in job market evaluation by applicants. Level of Evidence: Level V.